Pancadaya Transformation as a Catalyst for Empowerment-Based Collective Economic Independence and Prosperity in Indonesia - Dharma Setyawan; Dwi Nugroho; Suhono, Suhono; Mowafg Abrahem Masuwd (International Journal of Community Engagement Payungi, 2025)
This research explores community-based economic transformation through case studies of Pasar Yosomulyo Pelangi (Payungi) in Metro, Pasar Papringan in Temanggung, and Pasar Kamu in Deli Serdang. These three markets exemplify an alternative model of people-centered economic development grounded in the Pancadaya principles knowledge, sacrifice, movement, culture, and welfare—within a collective empowerment framework. The findings reveal that this approach not only enhances financial well-being but also fosters social solidarity, cultural revitalization, and ecological sustainability. Empowerment emerges through a praxis-based mechanism that integrates critical reflection and collective action, inspired by the emancipatory philosophies of Paulo Freire and Tan Malaka. In these market spaces, citizens act not only as economic agents but also as active learners and educators, cultivating agency, awareness, and alternative economic practices. Each site demonstrates localized strengths: Payungi excels in critical consciousness, transformative education, and multidimensional welfare; Papringan stands out for ecological awareness and innovative local currency systems; while Pasar Kamu contributes significantly to MSME empowerment and digital adaptation. This study contributes a novel theoretical framework Pancadaya Transformation for understanding community empowerment as an integrative process of economic, cultural, educational, and ecological development. It advances the discourse on alternative development by demonstrating how grassroots market spaces can function as educational arenas, cultural incubators, and engines of equitable growth. As such, Pancadaya offers a replicable, value-driven model for sustainable economic transformation rooted in local wisdom and participatory action, particularly relevant for the Indonesian context and other Global South settings.